2018
DOI: 10.1103/physrevd.98.025005
|View full text |Cite
|
Sign up to set email alerts
|

Ground states of a Klein-Gordon field with Robin boundary conditions in global anti–de Sitter spacetime

Abstract: We consider a real, massive scalar field both on the n-dimensional anti-de Sitter (AdS n ) spacetime and on its universal cover CAdS n . In the second scenario, we extend the recent analysis on PAdS n , the Poincaré patch of AdS n , first determining all admissible boundary conditions of Robin type that can be applied on the conformal boundary. Most notably, contrary to what happens on PAdS n , no bound state mode solution occurs. Subsequently, we address the problem of constructing the two-point function for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 35 publications
(59 reference statements)
1
66
0
Order By: Relevance
“…These boundary conditions appear frequently in the physics literature; see e.g. [DF2,DFM]. Further motivation comes from the study of the Dirichlet-to-Neumann operator, which was recently shown to coincide with a power of the wave operator in the case of a static metric [EdMGV].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…These boundary conditions appear frequently in the physics literature; see e.g. [DF2,DFM]. Further motivation comes from the study of the Dirichlet-to-Neumann operator, which was recently shown to coincide with a power of the wave operator in the case of a static metric [EdMGV].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In [1,2] it was used that the frequencies corresponding to Dirichlet come equispaced by 2n, with n an integer number [26], and this implied immediately the spacelike support of K. Such a simplification does not occur with Robin boundary conditions, since the frequencies are given by the transcendental equation above and are not equispaced (see [12] as well as [13]). However by the analytic continuation method we will employ, it will be easy to construct K for Neumann boundary condition γ = π/2 and then for generic Robin boundary conditions, and we will see they have spacelike support.…”
Section: Short Review Of Klein-gordon Modes In Adsmentioning
confidence: 99%
“…earlier results of [12] and the recent work of [13], we consider Robin boundary conditions. Immediately we will see the need to proceed with care, since divergences appear when imposing Neumann boundary conditions (Φ ∼ z ∆ − ), at least when working in position space.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This includes for example compactifications of antide Sitter spacetime with appropriate conditions on its timelike boundary (cf. [8,9] for a recent discussion of boundary conditions on anti-de Sitter spacetime and spacetimes with a timelike boundary).…”
Section: Introductionmentioning
confidence: 99%